New frontiers in Iranian Archaeology: digital technology and cultural heritage - Álvarez-Mon, J. (ISIMU, 2016)
Inspired by my recent work in iran - were I was able to compile a digital corpus of material culture related to the ancient Iranian civilization of Elam - I stipulate and encourage archaeological and museological objectives cognizant of twenty-first-century challenges. At its core, this vision is compelled by a philosophical understanding of the museum as a research and didactical institution, while critically considering the complex relationships between museums and politics and the imperative need to merge computer literacy with a sound understanding of the material at hand. At the end it is the archaeologist, I argue, that through our privileged role as interpreters of the material past, together with a full awareness of present cultural realities, is uniquely positioned to advocate for fully-implemented digital museum systems which would make archaeological collections truly accessible to a global audience.